Pembelajaran Dengan Pendekatan Science, Technology, Engineering, and Mathematic (STEM) dalam Meningkatkan Kemampuan Literasi Sains Pada Materi Redoks - Hidayatullah, Wahyu Nur; Mitarlis, Mitarlis (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2024)
In 21st century education requires students to be able to master various abilities in science learning, one of them is scientific literacy skills. To be able to develop scientific literacy skills in science learning, an approach is needed in its learning, one of the efficient approaches to be applied is the STEM (science, technology, engineering, and mathematics) approach. The method applied in this article is the Systematic Literature Review (SLR), this method is carried out by reviewing 20 articles with publication years from 2013 - 2024, which focus on STEM learning in improving scientific literacy skills in redox material. The article search method is carried out through several document sources from SINTA, google scholar, crossref, ERIC, and SCOPUS. In the initial search, the article began with a keyword search: STEM approach, scientific literacy, and redox. Data analysis was conducted by analyzing articles related to 1) the relationship between the STEM approach and scientific literacy, 2) the relationship between redox learning and scientific literacy, 3) the relationship between the STEM approach and redox learning, 4) the influence of learning with the STEM approach on scientific literacy skills in redox material. The results of the review showed that the STEM approach can develop students' scientific literacy skills as shown by 11 articles; the STEM approach to redox learning has proven effective and received a positive response from students as shown in 5 articles; redox learning with several learning models can improve scientific literacy as shown in 3 articles. However, the relationship between the STEM approach, scientific literacy, and redox has not been found, this is an opportunity for further research on the implementation of the STEM approach to scientific literacy in redox material.